EFFECTIVENESS OF BROWN SEAWEED (Sargassum sp.) AS NATURAL ANTIOXIDANT FOR ENDOTHELIAL CELL PROTECTION IN PREECLAMPSIA: A LITERATURE REVIEW - Lia Arian Apriani; Ida Ariyanti (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Seaweed as one of the natural resources has many potential bioactive ingredients. One of them is Phaeophyceae which shows the highest antioxidant activity among other seaweed. Sargassum sp has many potential bioactive ingredients in the pharmaceutical field which has been supported by several scientific studies. This study aims to expose all information related to abilities Sargassum sp as an antioxidant for endothelial cell protection in preeclampsia in a comprehensive and systematicmanner. Methods: This study was a systematic review that used the prism protocol. Data obtained from Electronic databases Science Direct, Springer, DOAJ, NCBI and Google Scholar that published between 2009 and 2019. By using keywords such as an antioxidants of Sargassum sp, preeclampsia and antioxidants, as well as antioxidants and endothelial cells to find the relevant journal. Results: The search found 963 articles, of which 215 articles were included in the inclusion and exlusion criteria. The final results obtained 8 articles that are suitable for this literature review. Majority of studies used the same method namely experimental, 3 other studies uses meta-analysis randomized controlled trials, and a case-control study. Analysis of the studies found out that Sargassum sp contains phenolic compounds which function as antioxidants in fighting free radicals and as protection againstendothelial cells in preeclampsia. Conclusion: Sargassum sp is proven to have the value of high antioxidant effect that is able to fight free radicals and is able to protect endothelial cells in preeclampsia. Therefore, this study is presented to assist researchers in planning their future studies related to seaweed in preventing preeclampsia in the fields of obstetrics and gynecology and with the hope of potential future drug development. Keywords: Sargassum sp, Antioxidants, Endothelial Cells, Preeclampsia